AMLODIPINE IN CORRECTION OF HIGH RISK ARTERIAL HYPERTENSION: FOCUS ON MECHANISMS OF INFLAMMATION - A. A. Tarasov; S. I. Davydov; T. A. Bezborodova; M. A. Gordeeva; A. R. Babaeva (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study the effect of amlodipine on the main indicators of systemic inflammation and its safety in patients with arterial hypertension (HT) in combination with ischemic heart disease (IHD) or diabetes mellitus (DM) type 2. Material and methods. Patients with HT (2-3 degree) associated with IHD or DM type 2 were included into the study. Patients were randomized into main group (n=30) receiving amlodipine 5-10 mg daily in addition to standard therapy (ACE inhibitors, beta-blockers, aspirin, statins, hypoglycemic agents), or into control group (n=30) receiving only standard therapy. Efficacy and safety of the therapy was evaluated by clinical, instrumental and laboratory parameters. Dynamics of interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α and C-reactive proteine (CRP) levels were determined to evaluate the activity of systemic inflammation. Treatment duration was 6-8 weeks. Results. Blood pressure reduction by 17.1±5.8/11.4±4.0 mmHg (p<0.05) was revealed in the main group and by 13.6±4.7/8.9±5.3 mm Hg - in the control one. A number of angina pectoris daily episodes decreased from 2.4±0.3 to 1.8±0.2 in the main group and from 2.2±0.2 to 2.0±0.4 in the control group. Angina attacks duration also decreased from 2.3 to 1.25 min in the main group. Significant reduction of IL-6 blood level from 16.6 (5.0; 22.5) to 6.5 (1.6; 12.7) pg/ml (p<0.05) and CRP blood level from 7.45 (2.56; 9.54) to 5.35(3.45; 6.23) mg/l (p<0.05) was observed in the main group (data is presented as median and interquartile range in the bracket). Blood levels of these inflammatory markers did not change significantly in the control group: IL-6 from 19.7 (7.3; 29.6) to 22.5 (13.6; 48.3) pg/ml, CRP from 6.85 (3.85; 8.23) to 7.05 (3.15; 9.12) mg/ l. Treatment tolerability was comparable in the groups.  Conclusion. Amlodipine is effective and safe antihypertensive agent. It reduces systemic pro-inflammation activity , which can promote atherosclerosis progression. Therefore, amlodipine can be recommended as first-line drug for the treatment of HT associated with DM and IHD.